Religious Dimensions of Confucius’ Teachings on Ren and Li in the Analects - Jongtae Lee (Religions, 2024)
This essay examines whether Confucius aligns more with humanism or religious thought, asserting that his philosophy defies simple classification. It highlights his use of religious motifs, especially the concept of li 禮, which he broadened beyond mere rituals to include societal behaviors, infusing them with a sacred essence. Additionally, this essay delves into Confucius’s notion of de 德, perceived as having an almost magical influence without coercion, closely tied to his ideas on li and governance. This reflects a belief in a universal moral order, challenging the view of Confucius as purely a humanist. The text also explores his nuanced understanding of tian 天, a central yet complex aspect of his philosophy, suggesting a spiritual dimension. Ultimately, this essay advocates for recognizing Confucius not only as a moral guide but as a thinker embodying significant religious or spiritual insights.